Novel application of β-cyclodextrins in textile dyeing processes - Soares, Graça M. B. (2008)
A new important application field of β-cyclodextrins is the textile dyeing technical process. Their ability to form inclusion complexes with textile dyes is guaranteed by the modification of physical and chemical properties. The possibility of host-guest associations between cyclodextrins and dyes allows modifications of features like: solubility, stability or even affinity of organic dyes for the textile materials. The production of fluorescent cellulosic materials is conditioned by the unavailability of dyes in market for these propose with a single exception of the Remazol Luminous Yellow FL. The aim of the work was to find out suitable method of dyeing fluorescent cellulosic fibers using available fluorescent dyes for the dyeing of synthetic fibers. Two different commercial β-cyclodrextrins, methylated and hydroxypropilated cyclodextrins, were tested in a dyeing process using Rhodamine B as model dye. The influence of process parameters such as pH, cationic agent, CD type and concentration were analysed. It was found that the two-step method, consisting of one impregnation process with CD-dye complexes, at alkaline pH and room temperature followed of a fixation step (180ºC, 1min) is the most convenient process to obtain fluorescent dyed fabrics with suitable performance. The obtained results demonstrate that the cotton could be dyed using β-cyclodextrins based process with good balance between washing fastness properties and mechanical properties of dyed fabrics.